Comparison of Efficacy between Open and Close Reduction in Supracondylar Fracture of Humerus in Children Using Flynn’s Criteria - Rashid Muhammad, Dost Mohammad Sohu, Zamir Ahmed Soomro, Kashif Ali Shaikh, Suresh Kumar, Hafeez Ullah Ghumro, Fazallullah Mahar, Aijaz Ali Maitlo (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare the efficacy between open and close reduction in supracondylar fracture of humerus in children using Flynn’s criteria. Study Design: Randomized control trial. Place and Duration of Study: Department of Orthopaedic Surgery, Chandka Medical College Hospital, Larkana from 1st April 2019 to 31st March 2022. Methodology: One hundred patients were enrolled and divided into two groups (open reduction and closed reduction groups). Each group had 50 patients. Fracture-fragments which were reduced through open reduction protocol or closed reduction were operated under highly standardized care and fixation was performed through K wiring in cross wise pattern. Results: Most of the children were male in both groups with only 20 and 24% females in open and closed reduction groups respectively. The efficacy analysis presented that open reduction efficacy was only 8-10 percent respectively in 5-10 and 11-15 years children respectively. The Flynn criteria also presented that 31 cases of open reduction were having an excellent grade followed by 14 with good. Conclusion: Open reduction method to be superior over closed reduction with higher number of satisfactory scores and efficacy. Keywords: Efficacy, Supracondylar fracture, Flynn’s criteria, Open reduction, Close reduction